English Language Learners: Just Job Seekers or Leaders? - Khatri, Man Bahadur (IJRDO- Journal of Educational Research, 2016)
People call English a crazy language but research studies have found people are crazy for English language all over the world. Many people speak English and it has been working as a lingua franca in every function in the world where people of different countries/language backgrounds are met. Sometimes people are found roaming for jobs in the market after completion of Master’s in English Language Teaching form recognized universities. They are found quite frustrated. In such cases they are to be envisioned with some good opportunities and made optimistic, courageous and risk takers. Some people can have good qualification, skills and desires but they might not have got opportunities. They might have been lacking behind because of the lack of access to information, encouragement and guidance. For them, this article can become a direction, hope of ray, trail for destination and oasis for optimism. English Language Learners can become good entrepreneurs, leaders, counselors, mentors, motivators, administrators and so on. But, not just a job seekers and passive employees in 21st century.